GAMIFICATION AND BLOCKCHAIN-BASED REWARD SYSTEMS FOR MOTIVATING MATH MASTERY IN EBONYI STATE (IJOVTECH, 2026)
The teaching/learning of mathematics in Ebonyi State, Nigeria is consistently associated with such challenges as low student motivation, low performance in national exams, lack of teaching material, and high math anxiety among secondary school students. This paper is an investigation into how the concept of gamification and blockchain-based reward systems can be achieved as a new intervention in developing intrinsic and extrinsic motivation to master mathematics. The study was based on self-determination theory and flow theory using a mixed-method quasi-experimental design of the pretest- posttest control group factors. Students in six public secondary schools in the senatorial zones of Ebonyi North, Central, and South (320 students: 52% female, 48% male) by socioeconomic status (low: 62 percent, middle: 28 percent, high: 10 percent) and school location (rural: 65 percent, urban: 35 percent) were included. Primary data were obtained through the questionnaires, achievement tests, semi-structured interviews, and blockchain transaction logs based on a tailored prototype application that rewarded non-fungible tokens (NFTs) and mortaby-like points upon completing math tasks. Findings showed that motivation scores (t(318) = 8.42, p <.001, d = 0.94), and math performance (mean improvement of 24.6% in experimental group and 7.2% in control) significantly improved. Rewards were guaranteed to be transparent and non-alterable with the help of blockchain, which promoted the sense of fairness and sustainability. There were issues of disparities in digital access and early technical barriers. The results may point to the idea that gamified blockchain systems can become the solution to change the way mathematics are taught in the settings where the available resources are scarce such as Ebonyi State to facilitate the equitable motivation and mastery. Such recommendations are the policy integration of digital tools and educator education.